Fast piezoresistive sensor and UV photodetector based on Mn‐doped ZnO nanorods. Issue 1 (17th November 2014) - Chey, Chan Oeurn; Liu, Xianjie; Alnoor, Hatim; Nur, Omer; Willander, Magnus
<x xml:space="preserve">Abstract</x> A low cost hydrothermal synthesis method to synthesize Mn‐doped ZnO nanorods (NRs) with controllable morphology and structure has been developed. Ammonia is used to tailor the ammonium hydroxide concentration, which provides a source of OH– for hydrolysis and precipitation during the growth instead of HMT. The morphological, chemical composition, structural, and electronic structure studies of the Mn‐doped ZnO NRs show that the Mn‐doped ZnO NRs have a hexagonal wurtzite ZnO structure along the c‐axis and the Mn ions replace the Zn sites in the ZnO NRs matrix without any secondary phase of metallic manganese element and manganese oxides observed. The fabricated PEDOT:PSS/Zn0.85Mn0.15O Schottky diode based piezoresistive sensor and UV photodetector shows that the piezoresistive sensor has pressure sensitivity of 0.00617 kPa–1 for the pressure range from 1 kPa to 20 kP and 0.000180 kPa–1for the pressure range from 20 kPa to 320 kPa with relatively fast response time of 0.03 s and the UV photodetector has both relatively high responsivity and fast response time of 0.065 A/W and 2.75 s, respectively. The fabricated Schottky diode can be utilized as a very useful human‐friendly interactive electronic device for mass/force sensor or UV photodetector in everyday living life. This developed device is very promising for small‐size, low‐cost and easy‐to‐customize application‐specific requirements. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)